Incorporating Culture into Listening Comprehension Through Presentation of Movies - Kusumarasdyati Kusumarasdyati (TEFLIN Journal: A publication on the teaching and learning of English, 2005)
Abstract: The use of movie videos as an instructional aid in the teaching of English as a foreign language (EFL) should be encouraged due to variÂous pedagogical benefits. This article attempts to suggest a technique of utilizing movies in English listening classes in order to improve the aural perception skills of the learners. It comprises three stages: previewing, viewing and postviewing. In the previewing stage, learners read a brief description of the theme of the movies to activate their prior knowledge, guess the meaning of certain keywords presented in sentential contexts, or familiarize themselves with the main characters. Next, the learners view the movies---either with or without any subtitlesâand while doing so they are supposed to answer several questions in written form. Finally, the learners are engaged into a postviewing activity in the form of contrasting cultures reflected in the movies. This technique of teaching listening has proved to be effective in developing listening skills in a foreign language and sensitizing them to the target culture, which is an inseparable aspect of language learning.